Գրիգոր Խլաթեցու երաժշտաբանաստեղծական ժառանգությունը - Մուշեղյան, Աստղիկ («Նաիրի» հրատ.)
Григор Церенц Хлатеци (1349-1425) был не только знаменитым церковным и общественным деятелем, но и историографом, поэтом, миниатюристом, писцом, комментатором, редактором и педагогом. Он был также блестящим музыкантом, искусным певцом и владел искусством хазового письма. Хлатеци внес ощутимый вклад в редактирование Гандзарана (сборника Праздничных песнопений), пересмотрел его в соответствии с изменениями и пополнениями, внесенными в армянский Церковный календарь, обогатил книгу новыми единицами и отредактировал старые. Кроме того он является также автором большого количества духовных песен (гандз, таг, мегеди, ордорак), посвященных праздникам Господним, святым Вселенской церкви и Армянской Апостольской церкви, а также армянским мученикам. В статье уточняется список песнопений Хла- теци в соответствии с его автографами. Grigor Tzerents Khlatetsi (1349-1425) was not only a famous clergyman and public figure, but also historiographer, poet, miniaturist, scribe, commentator, editor and pedagogue. He was at the same time a brilliant musician, a good singer and a man skilled in khaz (neuma) writing. Khlatetsi contributed a lot to the new recension of the Gandzaran (Miscellany of Festive Chants); he revised and brought it into correspondence with the changes and additions introduced in the Armenian Church Calendar. He enriched the book with new units and edited the old ones. He is also the author of a great number of sacred chants (gandz, tagh, meghedy, hordorak) devoted to the Dominical Feasts and to saints of the Universal Church and the Armenian Apostolic Church, as well as to Armenian martyrs. The present article specifies the list of Khlatetsi‟s sacred chants in accordance with his autographs.
Keywords: Երգարվեստ; Կենսագրություն